Carcinoma de próstata: estudio comparativo entre gammagrafía ósea y resonancia nuclear magnética para metástasis ósea - Cruz Brito, Jorge Enrique (Machala : Universidad Técnica de Machala, 2018)
Introduction: Prostatic carcinoma is caused by the mutation of prostate cells thus altering their physiological development, these pathogenic cells are propagated via Hematogenous or lymphatic at bone level where produced metastases. Currently, carcinoma of the prostate has a high incidence in men age around the world. According to the American Cancer Society, the risk in men prostate cancer is one in seven. Objective: to evaluate the diagnostic value between bone scintigraphy and MRI in patients with bone metastases carcinoma of the prostate. Methodology: 31 articles of journals indexed on data platforms were selected, such as: PubMed, Google Scholar, web of Science, Medscape and Scielo, published during the last five years in relation to the topic of study. Result: the information that was obtained between the bone scans and magnetic resonance imaging shows its advantages and limitations thereby improving diagnostic and therapeutic decisions. Conclusions: it is concluded that magnetic resonance is an image technique superior to bone scintigraphy because it presents greater sensitivity and specificity besides its great utility in: early detection, diagnosis, monitoring, evaluation of response to treatment, malignant tumor staging and tumor recurrence. Recommendations: we propose a diagnostic algorithm for the suspicion of bone metastasis, thus fulfilling the objective of an early diagnosis.
Introducción: El carcinoma prostático es causado por la mutación de células prostáticas alterando así su desarrollo fisiológico, estas células patógenas se propagan por vía hematógena o linfática a nivel óseo donde produce metástasis. Actualmente, el carcinoma de próstata tiene una alta incidencia en hombres mayores en todo el mundo. Según la Sociedad Estadounidense del Cáncer, el riesgo en hombres de padecer cáncer de próstata es uno de cada siete. Objetivo: evaluar la utilidad diagnóstica entre gammagrafía ósea y resonancia nuclear magnética en pacientes con metástasis ósea por carcinoma de próstata. Metodología: Se seleccionaron 31 artículos de revistas indexadas en plataformas de datos, tales como: PubMed, Google Académico, web of Science, Medscape y Scielo publicadas durante los últimos cinco años en relación con el tema de estudio. Resultado: La información que se obtuvo entre la Gammagrafía ósea y resonancia nuclear magnética muestra sus ventajas y limitaciones, mejorando así la toma de decisiones diagnósticas y terapéuticas. Conclusiones: se concluye que la resonancia magnética es una técnica de imagen superior a la gammagrafía ósea porque presenta mayor sensibilidad y especificidad además de su gran utilidad en: detección temprana, diagnóstico, monitorización, evaluación de respuesta al tratamiento, estadificación tumoral maligna y recidiva tumoral. Recomendaciones: proponemos un algoritmo de diagnóstico para la sospecha de metástasis ósea, cumpliendo así el objetivo de un diagnóstico precoz.
Keywords: CARCINOMA; PROSTATA; METASTASIS; GAMMAGRAFIA